Real Life Clinical Management and Survival in Advanced Cutaneous Melanoma: The Italian Clinical National Melanoma Registry Experience - Crispo, Anna; Corradin, Maria Teresa; Giulioni, Erika; Vecchiato, Antonella; Del Fiore, Paolo; Queirolo, Paola; Spagnolo, Francesco; Vanella, Vito; Caracò, Corrado; Tosti, Giulio; Pennacchioli, Elisabetta; Giudice, Giuseppe; et al. (Frontiers in Oncology, 2021)
Background: Cutaneous melanoma (CM) is one of the most aggressive types of skin cancer. Currently, innovative approaches such as target therapies and immunotherapies have been introduced in clinical practice. Data of clinical trials and real life studies that evaluate the outcomes of these therapeutic asso-ciations are necessary to establish their clinical utility. The aim of this study is to investigate the types of oncological treatments employed in the real-life clinical management of patients with advanced CM in several Italian centers, which are part of the Clinical National Melanoma Registry (CNMR). Methods: Melanoma-specific survival and overall survival were calculated. Multivariate Cox regression models were used to estimate the hazard ratios adjusting for confounders and other prognostic factors. Results: The median follow-up time was 36 months (range 1.2-185.1). 787 CM were included in the analysis with completed information about therapies. All types of immunotherapy showed a significant improved survival compared with all other therapies (p=0.001). 75% was the highest reduction of death reached by anti-PD-1 (HR=0.25), globally immunotherapy was significantly associated with improved survival, either for anti-CTLA4 monotherapy or combined with anti-PD-1 (HR=0.47 and 0.26, respectively) and BRAF+MEK (HR=0.62). Conclusions: The nivolumab/pembrolizumab in combination of ipilimumab and the addition of ant-MEK to the anti-BRAF can be considered the best therapies to improve survival in a real-world-population. The CNMR can complement clinical registries with the intent of improving cancer management and standardizing cancer treatment.